Individual-level factors predicting consumer financial behavior at a time of high pressure. (September 2016) - McNair, Simon; Summers, Barbara; de Bruin, Wändi Bruine; Ranyard, Rob
Abstract: Understanding the individual-level factors relating to consumer financial behaviors during periods of distinct pressure to spend may provide new insights as to the particular barriers people face in maintaining better control over their finances. Using Christmas as a focal example of a financially and psychologically pressured time, we collected survey data (N = 294) in the post-Christmas 2013 period, and investigated the extent to which levels of reported spending and borrowing in relation to Christmas could be predicted by sociodemographics, money management behaviors, and psychological factors such as coping style, locus of control, materialism, and spendthrift tendencies. A separate analysis examined the kinds of factors relating more specifically to money management behaviors. Spending was predicted by factors including external locus of control and spendthrift tendency. Emotional coping and denial coping predicted borrowing behavior, as did external locus of control. Money management behaviors predicted who borrowed, but were not related to amount borrowed. Spendthrift tendencies and materialistic values were predictive of less active money management. Our findings suggest that interventions to improve financial decision making might prove more effective if increased emphasis is placed on psychological issues such as developing coping skills and buffering agency. Highlights: We investigate spending, borrowing, and money management behavior at Christmas. Money management predicted having borrowed, but not amount of borrowing. Spendthrift tendency, and external locus of control each predicted higher spending. Emotional coping predicted who borrowed but denial coping predicted amount borrowed. Psychological resiliency may be an important factor in financial behavior.